Individual and combined association between nutritional trace metals and the risk of preterm birth in a recurrent pregnancy loss cohort - Liu, Yilin; Wang, Tingting; Ge, Yunpeng; Shen, Hongfei; Li, Jiapo; Qiao, Chong (Frontiers in Nutrition, 2023)
Background: Recurrent pregnancy loss (RPL) was associated with an elevated risk of pregnancy complications, particularly preterm birth (PTB). However, the risk factors associated with PTB in RPL remained unclear. Emerging evidence indicated that maternal exposure to metals played a crucial role in the development of PTB. The objective of our study was to investigate the individual and combined associations of nutritional trace metals (NTMs) during pregnancy with PTB in RPL.Methods: Using data from a recurrent pregnancy loss cohort (N=459), propensity score matching (1:3) was performed to control for covariates. Multiple logistic regression and multiple linear regression were employed to identify the individual effects, while elastic net regularization (ENET)and bayesian kernel machine regression (BKMR) were used to examine the combined effects on PTB in RPL.Results: Logistic regression model found that maternal exposure to copper (Cu) (quantile 4 [Q4] vs. quantile 1 [Q1], odds ratio [OR]: 0.21, 95% confidence interval [CI]: 0.05, 0.74) and zinc (Zn) (Q4 vs. Q1, OR: 0.19, 95%CI: 0.04,0.77) were inversely associated with total PTB risk. We further constructed environmental risk scores (ERS) using principal components and interaction terms derived from ENET model to predict PTB accurately (p < 0.001). In the BKMR model, we confirmed that Cu was the most This is a provisional file, not the final typeset article significant component (PIP=0.85). When other metals fixed at 25 th and 50 th percentiles, Cu was inversely associated with PTB. Besides, we demonstrated the non-linear relationships of Zn with PTB, and the potential interaction between Cu and other metals, including Zn, Ca, Fe.In conclusion, our study highlighted the significance of maternal exposure to NTMs in RPL and its association with PTB risk. Cu and Zn were inversely associated with PTB risk, with Cu identified as a crucial factor. Potential interactions between Cu and other metals (Zn, Ca, Fe) further contributed to understanding PTB etiology in RPL. These findings suggested opportunities for personalized care and preventive interventions to optimize maternal and infant health outcomes.